2007
DOI: 10.1124/jpet.107.121228
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Nicotine Differentially Regulates α6- and β3-Containing Nicotinic Cholinergic Receptors in Rat Brain

Abstract: We investigated the effects of chronic nicotine on ␣6-and ␤3-containing nicotinic acetylcholine receptors (nAChRs) in two rat brain regions using three methodological approaches: radioligand binding, immunoprecipitation, and nicotine-stimulated synaptosomal release of dopamine. Nicotine was administered by osmotic minipumps for 2 weeks. Quantitative autoradiography with [125 I]␣-conotoxin MII to selectively label ␣6* nAChRs showed a 28% decrease in binding in the striatum but no change in the superior collicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
123
5
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(146 citation statements)
references
References 47 publications
(91 reference statements)
17
123
5
1
Order By: Relevance
“…Nicotine administration also produces reward through DA release in the NAc, at least in part through stimulation of nAChRs in the ventral tegmental area (Blaha et al, 1996;Corrigall et al, 1994;Nisell et al, 1994;Yeomans and Baptista, 1997;Yoshida et al, 1993). Nicotinic acetylcholine receptors are widespread throughout the brain, with a rank order distribution of nAChR density being: thalamus > basal ganglia > cerebral cortex > hippocampus > cerebellum (Broussolle et al, 1989;Cimino et al, 1992;Clarke et al, 1984;Davila-Garcia et al, 1999;Dávila-García et al, 1997;London et al, 1995London et al, , 1985Pabreza et al, 1991;Pauly et al, 1989;Perry and Kellar, 1995;Valette et al, 1998;Villemagne et al, 1997).…”
Section: Functional Imaging Of Nicotinic Acetylcholine Receptorsmentioning
confidence: 99%
“…Nicotine administration also produces reward through DA release in the NAc, at least in part through stimulation of nAChRs in the ventral tegmental area (Blaha et al, 1996;Corrigall et al, 1994;Nisell et al, 1994;Yeomans and Baptista, 1997;Yoshida et al, 1993). Nicotinic acetylcholine receptors are widespread throughout the brain, with a rank order distribution of nAChR density being: thalamus > basal ganglia > cerebral cortex > hippocampus > cerebellum (Broussolle et al, 1989;Cimino et al, 1992;Clarke et al, 1984;Davila-Garcia et al, 1999;Dávila-García et al, 1997;London et al, 1995London et al, , 1985Pabreza et al, 1991;Pauly et al, 1989;Perry and Kellar, 1995;Valette et al, 1998;Villemagne et al, 1997).…”
Section: Functional Imaging Of Nicotinic Acetylcholine Receptorsmentioning
confidence: 99%
“…McCallum et al 184 did not observe upregulation of striatal a3*/ a6* receptor subunits, possible due to differences in nicotine exposure regimens and concentrations. Perry et al 185 reported downregulation of a6* receptors number and function in the striatum.…”
Section: General Overviewmentioning
confidence: 99%
“…172 a6-containing receptor a6* receptors response to chronic nicotine administration is not clear: some papers reports Upregulation, 165 whereas other papers report no change 184 or even downregulation. 185 b4-containing nAChRs *Less prone to receptor occupancy and desensitization, compared with a4b2* receptors. 16 …”
Section: Possible Missing Linksmentioning
confidence: 99%
“…The up-regulation is not accompanied by an increase in steady-state levels of subunit mRNA, indicating that the increase in receptors is independent of transcription or mRNA stabilization (25)(26)(27)(28). Studies in cells that heterologously express nAChRs suggest that nicotine acts as a "pharmacological chaperone," enhancing the incorporation of ␤2 subunits into assembling receptors (29,30) and thereby increasing the number of ␣4␤2 nAChRs and possibly changing the stoichiometry from (␣4) 3 (␤2) 2 to (␣4) 2 (␤2) 3 (31,32). The ability of nicotine to chaperone ␤2 subunits into the nAChR assembly appears to be due, in part, to an action of nicotine binding at a microdomain located on the extracellular portion of the ␤2 subunit (33).…”
Section: Neuronal Nicotinic Acetylcholine Receptors (Nachrs)mentioning
confidence: 99%
“…This ion flow, if sufficient, depolarizes neurons, which in turn contributes to CNS functions, such as cognition, affect, and reward, and activates important responses in the autonomic and sensory nervous systems. The predominant nAChRs in the mammalian brain contain ␣4 and ␤2 subunits (1)(2)(3)(4)(5), forming the ␣4␤2, ␣4␤2␣5, and perhaps other receptor subtypes (2, 4 -6).…”
Section: Neuronal Nicotinic Acetylcholine Receptors (Nachrs)mentioning
confidence: 99%